Unraveling the Mediating Factors in Agricultural Training Transfer for Ugandan Extension Workers - Mukasa, Pontious Mubiru; Miiro, Richard; Obaa, Bernard; Mutebi, Henry; Kizza, James; Kiwanuka, Joseph (East African Nature and Science Organization, 2025)
Purpose: This paper investigated the mediation role of transfer work environment and training design on training transfer of agricultural management skills on the population of extension. Work environment and training design are expected to mediate the relationship between trainee characteristics (independent variables) and the transfer of training (dependent variable). Methodology: Data was collected from 281 agricultural extension workers who completed training on holistic agricultural management skills training programs at Makerere universities. This was achieved through a survey questionnaire anchored on a 5-point Likert scale and analyzed using Structural equation modelling using Analysis of Moment of Structures. Findings: Based on the results; we established a positive significant relationship between trainee characteristics, work environment, training design and perceived training transfer as insinuated by the Learning Transfer System Inventory. Additionally, the work environment and training design of extension workers partially mediate the relationship between trainee characteristics and perceived training transfer as well as training design between work environment and perceived training transfer. Implications: To optimize training outcomes, attention should not only be given to individual trainee characteristics but also to the conducive work environment and well-designed training programs. Fostering a supportive work context and tailoring training designs to align with organizational needs become crucial strategies.